IMPLEMENTASI TEORI PERKEMBANGAN KOGNITIF BRUNER PADA PEMBELAJARAN MATEMATIKA TENTANG PERKALIAN DI KELAS II SEKOLAH DASAR - Lastini, Fitri; Sri Haryanti; Bambang Sumardjoko; Endang Fauziati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Research was carried out to describe and analyze the application of Bruner's cognitive development theory to mathematics learning about multiplication in elementary schools. Descriptive qualitative research method. The research was conducted at SDN 03 Ngepungsari with the research subjects being class teachers and class II students. Data was collected through interviews, documentation and observation and then analyzed according to the Milles and Hubberman model. The research results show that Bruner's theory of cognitive development can be applied to mathematics learning in elementary schools to enrich students' learning experiences in a more meaningful and contextual way. Through in-depth observations and interviews, it was found that the use of enactive, iconic and symbolic representations allows students to understand the concept of multiplication in stages, starting from manipulating concrete objects to using mathematical symbols, so that various factors that cause problems in learning mathematics can be minimized. Students understand the material more easily, are motivated to discover concepts independently according to their level of cognitive development, are more enthusiastic and active in learning. Thus, Bruner's approach has proven effective in creating an inclusive learning environment and supporting students' cognitive development at the elementary school level.